2021
DOI: 10.3390/su13137361
|View full text |Cite
|
Sign up to set email alerts
|

“I’ll Take the E-Scooter Instead of My Car”—The Potential of E-Scooters as a Substitute for Car Trips in Germany

Abstract: Considering the controversial discussion about the sustainability and usefulness of e-scooters, in this study, we analyzed the substitution potential of e-scooters, especially with regard to car trips. Based on data from the national mobility survey in Germany (Mobility in Germany, MiD 2017), we identified trips that could be covered purely by an e-scooter. Thereby, trip length, trip purposes, weather conditions, and other influencing factors were taken into account. Our analysis showed that, in Germany, 10–15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…In this section, we provide a few examples of how e-scooters could substitute motorised and non-motorised modes of transport. In terms of e-scooter impact on substituting motorised vehicles, Gebhardt et al (2021) conducted a study in Germany to investigate the feasibility of e-scooters as a substitute for car trips. Their findings indicated that e-scooters have the potential to replace approximately 10-15 % of motorised personal transport.…”
Section: The Impact Of E-scooters On Modal Shiftmentioning
confidence: 99%
“…In this section, we provide a few examples of how e-scooters could substitute motorised and non-motorised modes of transport. In terms of e-scooter impact on substituting motorised vehicles, Gebhardt et al (2021) conducted a study in Germany to investigate the feasibility of e-scooters as a substitute for car trips. Their findings indicated that e-scooters have the potential to replace approximately 10-15 % of motorised personal transport.…”
Section: The Impact Of E-scooters On Modal Shiftmentioning
confidence: 99%
“…There is still a lack of empirical research on both actual use and realistic potential. In a recent potential analysis for Germany, Gebhardt et al ( 2021) estimated a theoretical substitution potential of about 10% of all trips by motorized individual transport (MIT) by e-scooters, although this is an optimistic and certainly unrealized potential [32]. Selective data from various suppliers of e-scooters are available, but it is unclear to what extent they have been collected, evaluated, and interpreted in a scientifically well-founded manner.…”
Section: State Of the Artmentioning
confidence: 99%
“…Published research on e-scooters has increased significantly in the last four years [5,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Those e-scooter studies have focused on motivations for riding e-scooters [5,16,19]; sociodemographics and perceptions of e-scooter riders and non-riders [2,5,9,27]; route choice and infrastructure [20]; regulations of e-scooter systems [11,13,23]; mode replacement and multimodal connections with other modes [10,14,15,17]; or benefits and costs of e-scooter systems [5,12,16,18].…”
Section: Introductionmentioning
confidence: 99%
“…Published research on e-scooters has increased significantly in the last four years [5,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Those e-scooter studies have focused on motivations for riding e-scooters [5,16,19]; sociodemographics and perceptions of e-scooter riders and non-riders [2,5,9,27]; route choice and infrastructure [20]; regulations of e-scooter systems [11,13,23]; mode replacement and multimodal connections with other modes [10,14,15,17]; or benefits and costs of e-scooter systems [5,12,16,18]. Publications focusing on e-scooter parking are more limited and As shown above, prior research on e-scooter parking has focused on rider and nonrider perceptions of parking behavior, parking locations, cluttering of sidewalks and streets, as well as compliance with various types of regulations of e-scooter parking.…”
Section: Introductionmentioning
confidence: 99%